2020
DOI: 10.3390/ijms21176281
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Type 2: Variation in High-Density Lipoproteins Composition and Function

Abstract: Aims: Class A2 gestational diabetes mellitus (GDMA2) has short- and long-term effects on the mother and child. These may include abnormalities of placentation, damage to endothelial cells and cardiovascular disease. This research investigated the function and composition of high-density lipoproteins (HDL) among women with GDMA2 and their fetuses. Methods: Thirty pregnant women were recruited during admission for delivery. The function and expression of HDL, paraoxonase1 (PON1) and apolipoprotein A1 (APOA1) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Since apoM represents the main carrier of the vasoprotective S1P, the reduction of apoM on GDM HDL might contribute to endothelial dysfunction observed in GDM [ 208 ]. This was supported by another group using a migration assay with human umbilical vein endothelial cells [ 209 ]. Maternal GDM HDL showed less closure of cell migration, which was induced by TNF α, than control HDL [ 209 ].…”
Section: Pregnancy-related Diseases Affects Hdl Metabolism and Functionmentioning
confidence: 70%
See 2 more Smart Citations
“…Since apoM represents the main carrier of the vasoprotective S1P, the reduction of apoM on GDM HDL might contribute to endothelial dysfunction observed in GDM [ 208 ]. This was supported by another group using a migration assay with human umbilical vein endothelial cells [ 209 ]. Maternal GDM HDL showed less closure of cell migration, which was induced by TNF α, than control HDL [ 209 ].…”
Section: Pregnancy-related Diseases Affects Hdl Metabolism and Functionmentioning
confidence: 70%
“…This was supported by another group using a migration assay with human umbilical vein endothelial cells [ 209 ]. Maternal GDM HDL showed less closure of cell migration, which was induced by TNF α, than control HDL [ 209 ]. Levels of apoA-I as well as mass and activity of PON1 were significantly decreased in maternal GDM HDL [ 207 ], similar to another study [ 209 ].…”
Section: Pregnancy-related Diseases Affects Hdl Metabolism and Functionmentioning
confidence: 70%
See 1 more Smart Citation
“…Disorders associated with abnormal glucose metabolism (such as type 2 diabetes, GDM, etc.) not only involve abnormal glucose metabolism, but also abnormal lipid metabolism, especially for the damage and function of placental tissue, as well as the survival and development of offspring [22]. In our experiment, it was found that HL and HG could significantly cause damage to the placental tissue of mice, while the damage to the placental tissue of mice induced by HL and HG combined was more serious.…”
Section: Discussionmentioning
confidence: 50%
“…Pasternak et al [ 19 ] reported the function and composition of high-density lipoproteins (HDL) among women with class A2 GDM and their fetuses. They observed the changes in HDL both in maternal and placental samples but not in cord samples.…”
mentioning
confidence: 99%